On "defunct economists" and the use of economic ideas - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2022)
One Friday afternoon a dozen or so years ago I sat in on a freshman honors seminar led by one of my colleagues. This weekly seminar featured guest speakers from various walks of life, and that week's speaker was a state legislator who happened to be a member of the Republican party. At one point during his talk, the legislator emphasized that he was not a "Keynesian," for he was opposed to expansive government expenditures, seeing tax cuts as the path to economic growth. During the Q&A period that wound up the session, I raised my hand and, when called upon, informed our speaker that Keynes (1936), too, saw tax cuts as a tool for economic stimulus, meaning that our speaker was, unknowingly, a Keynesian. His reaction was one of disbelief, that I could not possibly be correct. Of course, he had never read Keynes. He had simply been taught that Keynesian economics meant big government and so was bad, and he was only too happy to parrot that line.
Keywords: 330